Rationale, Design, and Methods of the Action to Control Cardiovascular Risk in Diabetes Eye Study (ACCORD-EYE) - Chew, Emily Y.; Ambrosius, Walter T.; Howard, Letitia T.; Greven, Craig M.; Johnson, Samantha; Danis, Ronald P.; Davis, Matthew D.; Genuth, Saul; Domanski, Michael (The American journal of cardiology, 2007)
Diabetic retinopathy (DR) is a major microvascular complication of diabetes mellitus. The Action to Control Cardiovascular Risk in Diabetes Eye Study (ACCORD-EYE), a prospective study of a subset of patients in the randomized controlled clinical ACCORD trial, is being conducted at enrollment and after 4 years of follow-up to assess the progression of DR with standardized comprehensive eye exams and fundus photography of 7 standard stereoscopic fields. This study aims to assess the effects of the ACCORD medical treatment strategies of tight control of glycemia and blood pressure and management of dyslipidemia on the course of DR in patients with type 2 diabetes. Photographs will be evaluated at a centralized location using the modified Early Treatment Diabetic Retinopathy Study (ETDRS) classification. The primary outcome of ACCORD-EYE, which will measure the development and progression of DR, is a composite of (1) progression of DR (≥3 steps on the ETDRS scale), (2) photocoagulation for DR, or (3) vitrectomy for DR. Specifically, the following questions will be addressed: (1) Does a therapeutic strategy targeting a glycosylated hemoglobin (HbA 1c) level <6.0% reduce development and progression of DR more than one targeting an HbA 1c level of 7.0%–7.9% (target median level, 7.5%)? (2) In the context of good glycemic control, does a strategy using a fibrate to increase high-density lipoprotein cholesterol and lower triglyceride levels and a statin to maintain the level of low-density lipoprotein (LDL) cholesterol at <2.59 mmol/L (100 mg/dL) reduce development and progression of DR compared with one using placebo and a statin to treat LDL cholesterol? (3) In the context of good glycemic control, does a strategy targeting a systolic blood pressure level <120 mm Hg reduce development and progression of DR compared with one targeting a level <140 mm Hg? Secondary outcome variables include various levels of loss of visual acuity at 4 years versus baseline, cataract extraction, and the development or progression of diabetic macular edema. Methods to measure DR progression have been incorporated into ACCORD, and complete baseline data have been collected on 3,537 participants. These data will provide valuable information regarding the effects of medical treatment on the prevention and progression of DR.